Carbon / cobalt vanadate oxide composite material and preparation method and application thereof
By using carbon/cobalt vanadate oxide composite as negative electrode material in sodium ion batteries and capacitors, the problem of specific capacity decay and kinetic mismatch of electrode materials is solved, and a sodium ion capacitor with high energy density and high power density is realized performance.
Patent Information
- Application Number
- CN202411430992.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-14
- Publication Date
- 2025-01-07
AI Technical Summary
Sodium ion batteries and capacitors face the problem of specific capacity attenuation and mismatch between positive and negative electrode kinetics in the selection of electrode materials, which affects their performance.
The carbon/cobalt vanadate oxide composite material is synthesized by one-step solvothermal method and prepared by high-temperature calcination. The cobalt vanadate oxide in the carbon material is uniformly embedded in the porous structure to form a composite material and use it as the negative electrode material. Combining appropriate voltage windows and assembly of positive electrode materials, optimize the assembly process of sodium ion capacitors.
It significantly improves the specific capacity and rate performance of the negative electrode material of sodium ion battery, enhances the cycle stability, and obtains high energy density and high power density sodium ion capacitors by regulating the voltage window and the loading of active substances, and solves the positive and negative electrodes The problem of dynamic mismatch.
Smart Images

Figure CN119275271A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of energy storage devices, and in particular relates to a carbon / cobalt vanadate oxide composite material and a preparation method and application thereof. Background Art
[0002] Lithium-ion batteries have been widely used in electric vehicles, digital products, etc. However, the scarcity and high price of lithium resources have seriously affected the rapid development of the energy storage industry. Sodium resources are more abundant and cheaper than lithium resources, so the development of new energy storage devices such as sodium lithium-ion batteries and sodium ion capacitors is of great significance. On the one hand, it can serve as a supplement to energy storage devices such as lithium-ion batteries, and on the other hand, it also provides new directions and ideas for the efficient use of sodium resources. Electrode material is one of the important factors affecting the performance of sodium-ion batteries. Na + Bili + has a larger ionic radius, which results in Na + The embedding process is difficult and causes large volume changes, which results in extremely poor electrochemical properties of the material.
[0003] In order to solve this problem, the commonly used methods currently include carbon coating, nanostructure design, doping, and heterojunction construction. Among them, carbon coating is a method that can significantly alleviate the volume expansion of electrode materials, improve electronic conductivity, and enhance cycle stability and rate performance. In-situ carbon coating has the advantages of uniform carbon coating and adjustable coating thickness, which can achieve truly effective coating. Carbon coating design for bimetallic oxides can greatly improve the physical and electrochemical properties of electrode materials.
[0004] Although bimetallic oxides can exhibit a synergistic sodium storage mechanism in the energy storage process and have a high initial specific capacity, the Na + The rapid attenuation of the specific capacity of the electrode material caused by the size and volume changes during the cycle is a problem that must be faced. At the same time, sodium ion capacitors are also facing the mismatch problem between the positive and negative electrodes due to the different ion transfer rates, and the choice of electrode materials directly affects the performance of the device. How to solve the attenuation of the specific capacity of electrode materials and obtain sodium storage electrode materials with high specific capacity and excellent long cycle performance, and solve the problem of kinetic mismatch between the positive and negative electrodes of sodium ion capacitors, is of great significance. Summary of the invention
[0005] The main purpose of the present invention is to provide a carbon / cobalt vanadate oxide composite material and a preparation method and application thereof, so as to overcome the shortcomings of the prior art.
[0006] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention includes: One aspect of the present invention provides a carbon / cobalt vanadate oxide composite material, which includes cobalt vanadate oxide and a carbon material, wherein the carbon material has a porous structure, and at least a portion of the cobalt vanadate oxide is uniformly embedded in the porous structure of the carbon material.
[0007] Furthermore, part of the cobalt vanadate oxide carbon material is embedded in the porous structure of the carbon material, and part of it is exposed on the surface of the carbon material.
[0008] Furthermore, the carbon material includes at least a carbon matrix providing a porous structure and a carbon layer, the cobalt vanadate oxide is embedded in the porous structure of the carbon matrix to form a composite structure, and the carbon layer is coated on the surface of the composite structure.
[0009] Another aspect of the present invention provides a method for preparing a carbon / cobalt vanadate oxide composite material, the preparation method comprising: uniformly mixing a carbon source, a cobalt-containing compound, a vanadium-containing compound and a solvent, conducting a thermal reaction, and then calcining at a high temperature to obtain the carbon / cobalt vanadate oxide composite material.
[0010] Another aspect of the present invention also provides a carbon / cobalt vanadate oxide composite material prepared by the above preparation method.
[0011] Another aspect of the present invention also provides the use of the aforementioned carbon / cobalt vanadate oxide composite material as a negative electrode material.
[0012] Another aspect of the present invention also provides a negative electrode material, which includes the above-mentioned carbon / cobalt vanadate oxide composite material.
[0013] Another aspect of the present invention also provides the use of the aforementioned carbon / cobalt vanadate oxide composite material or the aforementioned negative electrode material in the field of energy storage devices.
[0014] Another aspect of the present invention provides a sodium ion capacitor, which includes a negative electrode, a positive electrode, an electrolyte and a separator between the positive electrode and the negative electrode, wherein the negative electrode includes the aforementioned negative electrode material.
[0015] Compared with the prior art, the present invention has at least the following beneficial effects: (1) The carbon / cobalt vanadate oxide composite material prepared by the present invention has cobalt vanadate oxide that can be evenly anchored on the carbon material. The carbon / cobalt vanadate oxide composite material has excellent specific capacity and rate performance when used as a negative electrode material for sodium ion batteries, and the cycle stability is significantly improved; (2) The sodium ion capacitor assembled by the present invention with carbon / cobalt vanadate oxide composite material as the negative electrode and active material as the positive electrode can obtain a sodium ion capacitor with high energy density and high power density by regulating the voltage window and the loading amount of active material, which provides a new idea for solving the problem of kinetic mismatch between positive and negative electrodes. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0017] Figure 1 is a flow chart for preparing carbon / cobalt vanadate oxide composite materials in some typical embodiments of the present invention; Figure 2a is Co in some typical embodiments of the present invention 2 VO 4 and Co 2 VO 4 XRD pattern of @CX (X=0.5, 1.0, 1.5); Figure 2b is Co in some typical embodiments of the present invention 2 VO 4 and Co 2 VO 4 @EDS diagram of CX (X=0.5, 1.0, 1.5); Figure 3a is Co in some typical embodiments of the present invention 2 VO 4 and Co 2 VO 4 @ CX (X = 0.5, 1.0, 1.5) specific surface area diagram; Figure 3b is Co in some typical embodiments of the present invention 2 VO 4 and Co 2 VO 4 @CX (X=0.5, 1.0, 1.5) pore size distribution diagram; Figure 3c is Co in some typical embodiments of the present invention 2 VO 4 @CX (X=0.5, 1.0, 1.5) carbon content thermogravimetric diagram; Figure 4a is Co in some typical comparative examples of the present invention 2 VO 4 SEM images of Figure 4b is Co in some typical comparative examples of the present invention 2 VO 4 TEM images of Figure 4c is Co in some typical comparative examples of the present invention 2 VO 4 Element distribution test diagram; Figure 4d is Co in some typical embodiments of the present invention 2 VO 4 SEM image of @C-1.5; Figure 4e is Co in some typical embodiments of the present invention 2 VO 4 @TEM image of C-1.5; Figure 4f is Co in some typical embodiments of the present invention 2 VO 4 @C-1.5 element distribution test diagram; Figure 5a is Co in some typical embodiments of the present invention 2 VO 4 and Co 2 VO 4 @CX (X = 0.5, 1.0, 1.5) at 100mA g -1 The specific capacity diagram below; Figure 5b is Co in some typical embodiments of the present invention 2 VO 4 and Co 2 VO 4 @CX (X=0.5, 1.0, 1.5) specific capacity diagram at different current densities; Figure 5c is Co in some typical embodiments of the present invention 2 VO 4 and Co 2 VO 4 @CX (X=0.5, 1.0, 1.5) at 500mAg -1 The long cycle performance test diagram below; Figure 6a is a schematic diagram of a sodium ion capacitor in some typical embodiments of the present invention; Figure 6b CV curves of sodium ion capacitors in some typical embodiments of the present invention under different voltage windows; Figure 6c CV curves of sodium ion capacitors in some typical embodiments of the present invention at different scan rates in a voltage window of 0.01-4.0V; Figure 6d1 is a constant current charge and discharge curve diagram of a sodium ion capacitor in some typical embodiments of the present invention at a current density of 0.05-1.0 A / g; Figure 6e is a graph of specific capacitance of sodium ion capacitors in some typical embodiments of the present invention at different current densities; Figure 6f The figure is a performance comparison chart of sodium ion capacitors in some typical embodiments of the present invention and other reported devices. DETAILED DESCRIPTION
[0018] In view of the problems existing in the above-mentioned prior art, after extensive and in-depth research by the inventors of the present invention, a carbon / cobalt vanadate oxide composite material and its preparation method and application are provided. The main purpose of the present invention is to select a reasonable carbon source, use a one-step solvothermal method to synthesize a cobalt vanadate oxide precursor containing a carbon source, and then obtain the carbon / cobalt vanadate oxide composite material by high-temperature calcination and carbonization. In addition, the present invention uses a carbon / cobalt vanadate oxide composite material as a negative electrode and an active material as a positive electrode to assemble a sodium ion capacitor. By regulating the voltage window and the amount of active material loaded, a sodium ion capacitor with high energy density and high power density can be obtained, which provides a new idea for solving the problem of kinetic mismatch between positive and negative electrodes.
[0019] The technical solution, its implementation process and principle will be further explained as follows.
[0020] As one aspect of the technical solution of the present invention, a carbon / cobalt vanadate oxide composite material is provided, comprising cobalt vanadate oxide and a carbon material, wherein the carbon material has a porous structure, and at least a portion of the cobalt vanadate oxide is uniformly embedded in the porous structure of the carbon material.
[0021] Furthermore, part of the cobalt vanadate oxide carbon material is embedded in the porous structure of the carbon material, and part of it is exposed on the surface of the carbon material.
[0022] Furthermore, the carbon material includes at least a carbon matrix providing a porous structure and a carbon layer, the cobalt vanadate oxide is embedded in the porous structure of the carbon matrix to form a composite structure, and the carbon layer is coated on the surface of the composite structure.
[0023] Furthermore, the pore size of the carbon material is 100-300 nm.
[0024] Furthermore, the cobalt vanadate oxide is a solid spherical particle with an irregular surface.
[0025] Furthermore, the particle diameter of the cobalt vanadate oxide is 10-50 nm.
[0026] Furthermore, the mass ratio of the elements Co, V and O in the carbon / cobalt vanadate oxide composite material is 3:2:9-6:5:12.
[0027] Furthermore, the specific surface area of the carbon / cobalt vanadate oxide composite material is 42.64-143.19 m 2 g -1 .
[0028] Furthermore, the carbon material content of the carbon / cobalt vanadate oxide composite material is 11.5-31.7%.
[0029] As another aspect of the technical solution of the present invention, a method for preparing a carbon / cobalt vanadate oxide composite material is provided, the preparation method comprising: uniformly mixing a carbon source, a cobalt-containing compound, a vanadium-containing compound and a solvent, conducting a thermal reaction, and then calcining at a high temperature to obtain the carbon / cobalt vanadate oxide composite material.
[0030] In some embodiments, the preparation method comprises: mixing the cobalt-containing compound and the solvent to obtain a first mixed solution; mixing the vanadium-containing compound and the solvent to obtain a second mixed solution; Mixing the first mixed solution and the second mixed solution to obtain a third mixed solution; The carbon source is added to the third mixed solution, a thermal reaction is carried out in situ, and then the carbon / cobalt vanadate oxide composite material is prepared after high-temperature calcination.
[0031] In some more specific embodiments, the preparation method specifically comprises: dissolving the cobalt-containing compound in a solvent, and performing a first stirring and mixing to obtain a first mixed solution.
[0032] In some preferred embodiments, the mass ratio of the cobalt-containing compound to the solvent is 00.0059-0.0120:1.
[0033] In some preferred embodiments, the first stirring time is 20-40 min, and the first stirring rate is 400-800 r / min.
[0034] In some preferred embodiments, the cobalt-containing compound includes any one of cobalt acetate tetrahydrate and the like, but is not limited thereto.
[0035] In some preferred embodiments, the solvent includes any one of ethylene glycol and the like, but is not limited thereto.
[0036] In some more specific embodiments, the preparation method further comprises: dissolving the vanadium-containing compound in a solvent, and performing a second stirring and mixing to obtain a second mixed solution.
[0037] In some preferred embodiments, the vanadium-containing compound includes any one of ammonium metavanadate and the like, but is not limited thereto.
[0038] In some preferred embodiments, the mass ratio of the vanadium-containing compound to the solvent is 0.00130-0055:1.
[0039] In some preferred embodiments, the second stirring time is 20-40 min, and the second stirring rate is 400-800 r / min.
[0040] In some more specific embodiments, the preparation method further comprises: mixing the first mixed solution and the second mixed solution by a third stirring step to obtain a third mixed solution.
[0041] In some preferred embodiments, the third stirring time is 20-40 min, and the third stirring rate is 400-800 r / min.
[0042] In some more specific embodiments, the preparation method further comprises: adding the carbon source to the third mixed solution, performing an in-situ thermal reaction to obtain a cobalt vanadate oxide precursor containing a carbon source, and then preparing the carbon / cobalt vanadate oxide composite material after high-temperature calcination in a vacuum inert atmosphere.
[0043] In some preferred embodiments, the carbon source includes at least any one of glucose, graphene, reduced graphene oxide, carbon nanosheets, etc., but is not limited thereto.
[0044] In some preferred embodiments, the temperature of the thermal reaction is 150-200° C., and the time of the thermal reaction is 12-24 h.
[0045] In some preferred embodiments, the high temperature calcination temperature is 400-600° C., and the high temperature calcination time is 2-5 hours.
[0046] In some more specific embodiments, the preparation method may include the following steps: The cobalt-containing compound is dissolved in a solvent, and the mixture is stirred at 400-800 r / min for 20-40 min to obtain a first mixed solution; the vanadium-containing compound is dissolved in a solvent, and the mixture is stirred at 400-800 r / min for 20-40 min to obtain a second mixed solution; the first mixed solution and the second mixed solution are stirred at 400-800 r / min for 20-40 min to obtain a third mixed solution; the carbon source is added to the third mixed solution, and the mixture is thermally reacted in situ at 150-200° C. for 12-24 h, washed and vacuum dried to obtain a cobalt vanadate oxide precursor containing a carbon source, and then the mixture is subjected to high-temperature calcination at 400-600° C. for 2-5 h in a vacuum inert atmosphere to prepare the carbon / cobalt vanadate oxide composite material.
[0047] As another aspect of the technical solution of the present invention, a carbon / cobalt vanadate oxide composite material prepared by the above-mentioned preparation method is also provided.
[0048] As another aspect of the technical solution of the present invention, there is also provided the use of the aforementioned carbon / cobalt vanadate oxide composite material as a negative electrode material.
[0049] As another aspect of the technical solution of the present invention, a negative electrode material is also provided, which includes the aforementioned carbon / cobalt vanadate oxide composite material.
[0050] In some embodiments, the specific capacity of the negative electrode material is 6.3-318.8 mAh / g.
[0051] In some embodiments, the negative electrode material has a current density of 50-3000 mA g -1 The number of cycles at the current density is 10-100.
[0052] In some embodiments, the negative electrode material has a -1 The Coulombic efficiency after 100 cycles at the current density was 37.8-53.9%.
[0053] As another aspect of the technical solution of the present invention, there is also provided application of the aforementioned carbon / cobalt vanadate oxide composite material or the aforementioned negative electrode material in the field of energy storage devices.
[0054] In some preferred embodiments, the energy storage device includes at least any one of a sodium ion capacitor, a sodium ion battery, etc., but is not limited thereto.
[0055] As another aspect of the technical solution of the present invention, a sodium ion capacitor is also provided, which includes a negative electrode, a positive electrode, an electrolyte and a separator between the positive electrode and the negative electrode, and the negative electrode includes the above-mentioned negative electrode material.
[0056] In some embodiments, the voltage window of the sodium ion capacitor is 0.01-4.4V.
[0057] In some particularly preferred embodiments, the voltage window is 0.01-4.0V.
[0058] In some embodiments, the sodium ion capacitor has a scan rate of 0.1-60 mV / s when the voltage window is 0.01-4.0 V.
[0059] In some embodiments, the sodium ion capacitor has a specific capacitance of 7.5-49.5 F / g at a current density of 0.05-20.0 A / g.
[0060] In some embodiments, the sodium ion capacitor has an energy density of 16.6-109.4 Wh / kg at a power density of 99.75-39900 W / kg.
[0061] In some embodiments, the mass ratio of the active material of the positive electrode to the negative electrode material in the sodium ion capacitor is 1:1-1:2.
[0062] The assembly method of the sodium ion capacitor is as follows: Sodium ion capacitors are placed in a glove box (O 2 Content <0.01ppm, water content <0.01ppm). Before assembly, the carbon / cobalt vanadate oxide composite electrode sheet needs to be assembled into a sodium ion half-cell and cycled for 5 to 10 cycles at a current density of 0.1A / g for pre-sodiumization. The specific assembly process of the sodium ion capacitor is as follows: First, the carbon / cobalt vanadate oxide composite electrode sheet with a pre-sodium active material thickness of 50 to 150μm is taken out from the half-cell, and then it is placed in the negative electrode shell as the negative electrode, and the electrolyte (1M NaPF 6 ), then put in two drops of glass fiber separator (GF / D), then drop in two drops of electrolyte, and then put in the positive electrode sheet with an active material thickness of 50~150μm, and finally put in the gasket, shrapnel, and positive electrode shell in turn. Use a sealed bag to take it out of the glove box, and finally use a packaging machine to package it. After standing for 12 hours, the electrochemical performance test is carried out.
[0063] In summary, the present invention prepares a carbon / cobalt vanadate oxide composite material by a one-step solvent thermal method and subsequent high-temperature calcination treatment, and characterizes its electrochemical performance when used as a negative electrode material for energy storage devices, and obtains the best carbon / cobalt vanadate oxide composite material by adjusting the amount of carbon source added. It has excellent specific capacity and rate performance when used as a negative electrode material for energy storage devices, and the cycle stability is significantly improved, and the application of modified bimetallic oxide-based materials in the field of energy storage devices is also expanded. In addition, the present invention optimizes the assembly process of sodium ion capacitors from the aspects of voltage window selection, positive electrode material selection, etc., and obtains the optimal conditions for assembling high-performance sodium ion capacitors, which provides a reference for the preparation and selection of negative electrode materials for sodium ion capacitors, and provides a new idea for solving the problem of mismatch between positive and negative electrode kinetics.
[0064] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with embodiment. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. Those skilled in the art can make modifications or equivalent substitutions based on the understanding of the technical scheme of the present invention without departing from the spirit and scope of the technical scheme of the present invention, and all should be included in the protection scope of the present invention.
[0065] If the specific experimental steps or conditions are not specified in the embodiments, the operations or conditions of the conventional experimental steps described in the literature in the field can be carried out. The reagents or instruments used without indicating the manufacturer are all conventional reagent products that can be obtained commercially. Exemplarily, the instruments needed for the test of the present invention are electrochemical workstation CHI660E (Shanghai Chenhua) and Blue Electric Tester (Wuhan Blue Electric Electronics Co., Ltd.). The electrochemical workstation CHI660E is used to test the voltage window range, specific capacitance and constant current charge and discharge curve of lithium ion capacitors, and the Blue Electric Tester is used to test the long cycle performance of sodium ion capacitors at high current density. The commercial purchase options of other raw materials and instruments not mentioned are all conventional choices and do not involve the core technical means of the present invention.
[0066] Example 1 261.6 mg Co(CH 3 COO 2 ·4H 2 O and 122.7 mg NH 4 VO 3Dissolve in 40mL ethylene glycol, stir at a magnetic stirring speed of 600r / min for 30 minutes to form solution I and solution II, then pour solution I into solution II, continue to stir at a magnetic stirring speed of 600r / min for 30 minutes, add a certain amount of 1.5g of anhydrous glucose, stir for another 30 minutes, and finally transfer into a 100mL polytetrafluoroethylene reactor and heat at 150, 180, and 200°C for 12, 18, and 24 hours, respectively. After cooling to room temperature, wash alternately with deionized water and anhydrous ethanol for 6 times, and finally put it in a vacuum drying oven at 60°C overnight to obtain a carbon source-containing cobalt vanadate oxide precursor. The carbon source-containing cobalt vanadate oxide precursor is then calcined at 400, 500, and 600°C in a vacuum tube furnace (filled with argon) for 2, 2.5, and 5 hours, respectively, to obtain the product carbon / cobalt vanadate oxide composite material (Co 2 VO 4 @CX). The optimal solvothermal temperature was determined to be 180°C, the optimal solvothermal time was 24 hours, the optimal calcination temperature was 500°C, and the optimal calcination time was 2.5 hours.
[0067] Example 2 The other operations were the same as those in Example 1, except that the carbon source was 0.5 g of anhydrous glucose, the thermal reaction conditions were heating at 180° C. for 24 hours, and the high-temperature calcination conditions were calcination at 500° C. for 2.5 hours.
[0068] Example 3 The other operations were the same as those in Example 1, except that the carbon source was 1.0 g of anhydrous glucose, the thermal reaction conditions were heating at 180° C. for 24 hours, and the high-temperature calcination conditions were calcination at 500° C. for 2.5 hours.
[0069] Example 4 Co 2 VO 4 When @CX (X=0.5g) is used as the negative electrode material, the test voltage is set to 0.01-3.0V, and its initial specific capacity at a current density of 100mA / g can reach 354.10mAh / g, and the specific capacity decays to 193.92mAh / g after 100 cycles. The specific capacity at 50mA / g-3000mA / g can reach 110.97-408.65mAh / g.
[0070] Example 5 Co 2 VO 4When @CX (X=1.0g) is used as the negative electrode material, the test voltage is set to 0.01-3.0V, and its initial specific capacity at a current density of 100mA / g can reach 482.38mAh / g, and the specific capacity decays to 204.03mAh / g after 100 cycles. The specific capacity at 50mA / g-3000mA / g can reach 100.61-493.51mAh / g.
[0071] Example 6 Co 2 VO 4 When @CX (X=1.5g) is used as the negative electrode material, the test voltage is set to 0.01-3.0V, and its initial specific capacity at a current density of 100mA / g can reach 458.21mAh / g, and the specific capacity decays to 237.18mAh / g after 100 cycles. The specific capacity at 50mA / g-3000mA / g can reach 121.00-499.45mAh / g.
[0072] Example 7 Carbon / cobalt vanadate oxide composite material (Co 2 VO 4 @C-1.5) as the negative electrode and activated carbon AC as the positive electrode to assemble the sodium ion capacitor (Co 2 VO 4 @C / / AC), the electrolyte is 1M NaPF 6 (dissolved in a mixture of ethylene carbonate, diethyl carbonate and dimethyl carbonate in a volume ratio of 1:1:1), the separator is a glass fiber membrane (GF / D), and in order to determine the optimal voltage window of Co2VO4@C / / AC, the voltage window is set to 0.01-4.0V, and the ratio of the active mass of the positive and negative electrodes is controlled at 1:1.5.
[0073] Example 8 The other operations are the same as those in Example 7, except that the voltage window is set to 0.01-4.2V.
[0074] Example 9 The other operations are the same as those in Example 7, except that the voltage window is set to 0.2-3.4V.
[0075] Example 10 The other operations are the same as those in Example 7, except that the voltage window is set to 0.2-3.6V.
[0076] Embodiment 11 The other operations are the same as those in Example 7, except that the voltage window is set to 0.2-3.8V.
[0077] Example 12 The other operations are the same as those in Example 7, except that the voltage window is set to 0.2-4.0V.
[0078] Example 13 The other operations are the same as those in Example 7, except that the voltage window is set to 0.2-4.2V.
[0079] Embodiment 14 The other operations are the same as those in Example 7, except that the voltage window is set to 0.2-4.4V.
[0080] Embodiment 15 The voltage window was set to 0.01-4.0V, and the ratio of the positive and negative active materials was controlled at 1:1.5. The maximum energy density of the sodium ion capacitor was determined to be 109.4Wh / kg at a power density of 99.75W / kg, and the minimum energy density was 16.6Wh / kg at a power density of 39900W / kg.
[0081] Example 16 The voltage window was set to 0.01-4.0V, and the mass ratio of the positive and negative active materials was controlled at 1:1.0. The maximum energy density of the sodium ion capacitor was determined to be 105.0Wh / kg at a power density of 99.75W / kg, and the minimum energy density was 24.3Wh / kg at a power density of 39900W / kg.
[0082] Embodiment 17 The voltage window was set to 0.01-4.0V, and the mass ratio of the positive and negative active materials was controlled at 1:2.0. The maximum energy density of the sodium ion capacitor was determined to be 75.3Wh / kg at a power density of 99.75W / kg, and the minimum energy density was 18.8Wh / kg at a power density of 39900W / kg.
[0083] Comparative Example 1 261.6 mg of cobalt acetate tetrahydrate (Co(CH 3 COO 2 ·4H 2 O) was dissolved in 40 ml of ethylene glycol and stirred for 0.5 h to form a uniform mixture to form solution I. Solution I was poured into solution II and stirred for 0.5 h to form an orange uniform solution, which was transferred to a 100 ml solvothermal reactor and reacted at 180 ° C for 24 h, then centrifuged, washed (washed three times alternately with deionized water and ethanol) and dried. Finally, it was calcined at 500 ° C in a tube furnace filled with argon for 2.5 h to obtain pure cobalt vanadate oxide (Co 2 VO 4 ).
[0084] Comparative Example 2 Pure Co 2 VO 4 When used as negative electrode material, the test voltage is set to 0.01-3.0V, and its initial specific capacity at a current density of 100mA / g can reach 328.24mAh / g, and the specific capacity decays to 33.52mAh / g after 100 cycles. The specific capacity at 50mA / g-3000mA / g can reach 6.3-354.19.0mAh / g.
[0085] Comparative Example 3 Pure Co 2 VO 4 As the negative electrode material, commercial activated carbon (AC) was used as the positive electrode material for Co 2 VO 4 / / Assembly of AC sodium ion capacitors, the test voltage is set to 0.01-4.0V, the mass ratio of positive and negative active substances is controlled at 1:1.5, and the maximum energy density of the sodium ion capacitor is 50.4Wh / kg at a power density of 99.75W / kg, and the minimum energy density is 9.2Wh / kg at a power density of 399000W / kg.
[0086] Figure 1 The preparation flow chart of carbon / cobalt vanadate oxide composite material is shown in FIG. Figure 2a For the synthesis of Co 2 VO 4 and Co 2 VO 4 @C XRD pattern, where the prepared Co 2 VO 4 Completely corresponds to PDF card 73-1633, but with different carbon source addition amounts of Co 2 VO 4 The XRD patterns of @CX (X=0.5, 1.0, 1.5g) only have strong carbon peaks, which is due to the thick carbon coating. 2 VO 4 The peak did not appear. Figure 2b Medium 2 VO 4 and Co 2 VO 4 The EDS results of @CX (X=0.5, 1.0, 1.5g) show that the atomic ratio of Co, V, and O in the material is about 2:1:4. 2 VO 4 @C was successfully synthesized.
[0087] The effect of carbon coating on the specific surface area of carbon / cobalt vanadate oxide composites can be obtained through BET testing. Figure 3a It can be seen that after adding the carbon source, when the carbon source addition amount is 0, 0.5, 1.0 and 1.5g, Co 2 VO 4 The specific surface areas of @C are 94.94, 51.16, 42.64 and 143.19 m 2 g -1 , it can be clearly found that Co 2 VO 4 The specific surface area is larger than that of Co 2 VO 4 @C-0.5 and Co 2 VO 4 @C-1.0 is large, mainly because the unmodified Co 2 VO 4 has more mesopores, and the Co prepared by the present invention 2 VO 4 @C's pore size is mainly large. Figure 3b YesCo 2 VO 4 and Co 2 VO 4 @CX (X = 0.5, 1.0, 1.5g) pore size distribution diagram, pore size distribution results and specific surface area results confirm the effect of carbon coating on the pore size of the composite material. At the same time, in order to determine the carbon coating amount of the material, the thermogravimetric test results show that Co 2 VO 4 The carbon contents of @CX (X=0.5, 1.0, 1.5g) are 11.5%, 25.0% and 31.7% respectively. Figure 3c shown.
[0088] Scanning electron microscopy (SEM) and transmission electron microscopy (TEM) were used to characterize the Co 2 VO 4 and carbon-coated Co 2 VO 4 The morphology and structure of @C were studied. Figure 4a and Figure 4b The image shows Co 2 VO 4 It is a nanoscale solid sphere with a rough surface. Figure 4d and Figure 4e The image shows Co 2 VO 4 @C, its modified Co 2 VO 4 The particle size becomes smaller, and the TEM image shows that the modified Co 2 VO 4 Evenly distributed in the carbon layer, which helps to inhibit Na +Volume expansion and material powdering caused by embedding materials. In addition, Figure 4c and Figure 4f The element distribution test diagram also shows that Co 2 VO 4 Co, V, O and Co 2 VO 4 @The Co, V, O, and C elements in C-1.5 are evenly distributed.
[0089] like Figure 5a As shown, Co 2 VO 4 and Co 2 VO 4 @CX (X = 0.5, 1.0, 1.5g) as negative electrode material, at 100 mA g -1 The specific capacities of the samples can reach 33.5, 193.9, 204.0 and 288.8 mAh g-1 at a current density of 100 cycles. -1 Moreover, the initial Coulombic efficiency increased from 37.8% to 53.9%. The increase in initial Coulombic efficiency indicates that the initial cycle Na + The reduction in losses and irreversible reactions directly indicates the supporting and conductive role of the carbon coating on the anode material during cycling. -1 When 2 VO 4 The specific capacities of @C-1.5 were maintained at 253.2, 234.5, 217.6, 198.8, 177.2, 149.3, and 124.0 mAh g -1 In addition, when the current density returned to 100 mA g -1 When the specific capacity is restored to 247.5 mAh g -1 , the results are as follows Figure 5b In addition, the Co 2 VO 4 and Co 2 VO 4 The cycling performance of @C material at high current density was found to be -1 After 500 cycles, Co 2 VO 4 and Co 2 VO 4 The specific capacities of @CX (X = 0.5, 1.0, 1.5 g) are 12.6, 124, 101.9, and 168.3 mAh g, respectively. -1 ,Co 2 VO 4@C specific capacity and Co 2 VO 4 The specific capacity of Figure 5c Based on these results, it can be seen that the carbon / cobalt vanadate oxide composite material significantly improves the conductivity of the electrode material, effectively alleviates the volume expansion, improves the interface stability, and increases the initial Coulombic efficiency.
[0090] The present invention finally determines that the optimal carbon source addition amount for preparing the carbon / cobalt vanadate oxide composite material is 1.5 g, the optimal solvent thermal temperature is 180° C. and the reaction time is 24 hours, and the optimal calcination temperature is 500° C. and the calcination time is 2.5 hours.
[0091] like Figure 6a The figure shows the schematic diagram of a sodium ion capacitor. During the charging process, Na+ moves to the negative electrode under the action of voltage, and PF 6 - Move toward the positive electrode. Figure 6b As shown, in order to determine the optimal test voltage window, the CV curves of sodium ion capacitors at 0.2-3.2V, 0.2-3.4V, 0.2-3.6V, 0.2-3.8V, 0.2-4.0V, 0.2-4.2V, 0.2-4.4V, 0.01-4.0V and 0.01-4.2V were tested respectively. Combined with polarization and electrolyte decomposition voltage, 0.01-4.0V was selected as the optimal voltage window. Figure 6c The CV curves of the sodium ion capacitor at different scan rates in the 0.01-4.0V voltage window show obvious rectangular shapes, indicating that the positive and negative electrodes of the sodium ion capacitor have a high degree of matching. Figure 6d The constant current charge and discharge curves of the sodium ion capacitor at different current densities also show obvious isosceles triangles, which further confirms that the positive and negative electrodes have a high match. Figure 6e As shown, it is found that the specific capacitance of sodium ion capacitors at 0.05, 0.1, 0.2, 0.4, 0.6, 0.8, 1.0, 2.0, 4.0, 6.0, 8.0, 10.0, 12.0, 14.0, 18.0 and 20.0 A / g can reach 49.5, 43.3, 30.8, 29.3, 27.7, 26.9, 26.1, 23.5, 20.1, 17.3, 15.2, 13.5, 12.0, 10.9, 9.6, 8.1 and 7.5 F / g, respectively. In addition, as Figure 6f As shown in the figure, the energy density of sodium ion capacitors can reach 109.5Wh / kg at a power density of 99.75W / kg; and at a high power density of 12kW / kg, its energy density can still be maintained at 38.2Wh / kg.
[0092] The present invention determines that the optimal voltage window of the sodium ion capacitor is 0.01-4.0 V, taking into account electrode polarization, electrolyte decomposition voltage and electrochemical performance. And based on the comparison of the performance of the assembled sodium ion capacitors, it is determined that the optimal ratio of the amount of positive and negative active materials of the sodium ion capacitor is 1:1.5.
[0093] The above results fully demonstrate the successful assembly of sodium ion capacitors and the excellent electrochemical properties they exhibit, and provide new ideas for the research of new negative electrode materials in the field of sodium ion batteries.
[0094] In summary, the present invention selects a reasonable carbon source, uses a one-step solvothermal method to synthesize a cobalt vanadate oxide precursor containing a carbon source, and then obtains a carbon / cobalt vanadate oxide composite material by high-temperature calcination and carbonization, and the cobalt vanadate oxide can be evenly anchored on carbon. And by regulating the amount of carbon source added, the carbon content of the material is regulated to obtain the optimal carbon / cobalt vanadate oxide composite material. When the carbon / cobalt vanadate oxide composite material is used as a sodium ion negative electrode material, its specific capacity after 100 cycles at 100mA / g can be maintained at 288.8mAh / g, even when the current density is 500mA / g, the specific capacity after 500 cycles is 168.3mAh / g. In addition, its rate performance is also extremely excellent, and the specific capacity at 3000mA / g is maintained at 124.0mAh / g. Sodium ion capacitors assembled with carbon / cobalt vanadate oxide composite materials as negative electrodes and active materials as positive electrodes can obtain sodium ion capacitors with high energy density and high power density by regulating the voltage window and the amount of active material loading. The modification study of cobalt vanadate oxide in the present invention shows that carbon material compounding is an effective way to improve the cycle stability and specific capacity of electrode materials.
[0095] The various aspects, embodiments, features and examples of the present invention should be considered as illustrative in all aspects and are not intended to limit the present invention, the scope of the present invention is defined only by the claims. Other embodiments, modifications and uses will be apparent to those skilled in the art without departing from the spirit and scope of the claimed invention.
[0096] In addition, the inventors of this case also referred to the aforementioned embodiments and conducted experiments with other raw materials, process operations, and process conditions described in this specification, and obtained relatively ideal results.
[0097] Although the present invention has been described with reference to illustrative embodiments, it will be appreciated by those skilled in the art that various other changes, omissions and / or additions may be made without departing from the spirit and scope of the present invention and that the elements of the embodiments may be replaced by substantial equivalents. In addition, many modifications may be made without departing from the scope of the present invention to adapt specific circumstances or materials to the teachings of the present invention. Therefore, it is not intended herein to limit the present invention to the disclosed specific embodiments for performing the present invention, but it is intended that the present invention will include all embodiments within the scope of the appended claims. In addition, unless specifically stated, any use of the terms first, second, etc. does not indicate any order or importance, but rather uses the terms first, second, etc. to distinguish one element from another element.
Claims
1. A carbon / cobalt vanadate oxide composite material, characterized in that: The invention comprises cobalt vanadate oxide and carbon material, wherein the carbon material has a porous structure, and at least a part of the cobalt vanadate oxide is uniformly embedded in the porous structure of the carbon material.
2. The carbon / cobalt vanadate oxide composite material according to claim 1, characterized in that: Part of the cobalt vanadate oxide carbon material is embedded in the porous structure of the carbon material, and part of it is exposed on the surface of the carbon material; And / or, the carbon material comprises at least a carbon matrix providing a porous structure and a carbon layer, the cobalt vanadate oxide is embedded in the porous structure of the carbon matrix to form a composite structure, and the carbon layer is coated on the surface of the composite structure; And / or, the pore size of the carbon material is 100-300 nm; And / or, the cobalt vanadate oxide is a solid spherical particle with an irregular surface; And / or, the particle diameter of the cobalt vanadate oxide is 10-50 nm; And / or, the atomic ratio of the elements Co, V and O in the carbon / cobalt vanadate oxide composite material is 3:2:9-6:5:12; And / or, the carbon / cobalt vanadate oxide composite material has a specific surface area of 42.64-143.19 m 2 g -1 ; And / or, the carbon material content in the carbon / cobalt vanadate oxide composite material is 11.5-31.7%.
3. A method for preparing a carbon / cobalt vanadate oxide composite material, characterized in that: include: The carbon source, the cobalt-containing compound, the vanadium-containing compound and the solvent are uniformly mixed, subjected to thermal reaction, and then calcined at high temperature to prepare the carbon / cobalt vanadate oxide composite material.
4. The preparation method according to claim 3, characterized in that: include: mixing the cobalt-containing compound and the solvent to obtain a first mixed solution; mixing the vanadium-containing compound and the solvent to obtain a second mixed solution; Mixing the first mixed solution and the second mixed solution to obtain a third mixed solution; The carbon source is added to the third mixed solution, a thermal reaction is carried out in situ, and then the carbon / cobalt vanadate oxide composite material is prepared after high-temperature calcination.
5. The preparation method according to claim 4, characterized in that: include: Dissolving the cobalt-containing compound in a solvent, and mixing by first stirring to obtain a first mixed solution; Preferably, the mass ratio of the cobalt-containing compound to the solvent is 0.0059-0.0120:1; Preferably, the first stirring time is 20-40 min, and the first stirring rate is 400-800 r / min; Preferably, the cobalt-containing compound comprises cobalt acetate tetrahydrate; Preferably, the solvent comprises ethylene glycol; And / or, the preparation method comprises: dissolving the vanadium-containing compound in a solvent, and mixing by a second stirring to obtain a second mixed solution; Preferably, the vanadium-containing compound comprises ammonium metavanadate; Preferably, the mass ratio of the vanadium-containing compound to the solvent is 0.0013-0.0055:1; Preferably, the second stirring time is 20-40 min, and the second stirring rate is 400-800 r / min; And / or, the preparation method comprises: mixing the first mixed solution and the second mixed solution by a third stirring step to obtain a third mixed solution; Preferably, the third stirring time is 20-40 min, and the third stirring rate is 400-800 r / min; And / or, the preparation method further comprises: adding the carbon source to the third mixed solution, performing an in-situ thermal reaction to obtain a cobalt vanadate oxide precursor containing a carbon source, and then preparing the carbon / cobalt vanadate oxide composite material after high-temperature calcination in a vacuum inert atmosphere; Preferably, the carbon source includes at least any one of glucose, graphene, reduced graphene oxide, and carbon nanosheets, and glucose is particularly preferred; Preferably, the temperature of the thermal reaction is 150-200°C, and the time of the thermal reaction is 12-24h; Preferably, the high temperature calcination temperature is 400-600°C, and the high temperature calcination time is 2-5h.
6. A carbon / cobalt vanadate oxide composite material prepared by the preparation method according to any one of claims 3 to 5.
7. Use of the carbon / cobalt vanadate oxide composite material according to any one of claims 1, 2 and 6 as a negative electrode material.
8. A negative electrode material, characterized in that A carbon / cobalt vanadate oxide composite material comprising any one of claims 1, 2, and 6; And / or, the specific capacity of the negative electrode material is 6.3-318.8 mAh / g; And / or, the negative electrode material is 50-3000mA g -1 The number of cycles under the current density is 10-100; And / or, the negative electrode material is at 100mA g -1 The Coulombic efficiency after 100 cycles at the current density was 37.8-53.9%.
9. Use of the carbon / cobalt vanadate oxide composite material according to any one of claims 1, 2, and 6 or the negative electrode material according to claim 8 in the field of energy storage devices; Preferably, the energy storage device includes at least any one of a sodium ion capacitor and a sodium ion battery.
10. A sodium ion capacitor comprising a negative electrode, a positive electrode, an electrolyte and a separator between the positive electrode and the negative electrode, characterized in that: The negative electrode comprises the negative electrode material according to claim 8; And / or, the voltage window of the sodium ion capacitor is 0.01-4.4V, preferably, the voltage window is 0.01-4.0V; And / or, the scanning speed of the sodium ion capacitor when the voltage window is 0.01-4.0V is 1-60mV / s; And / or, the sodium ion capacitor has a specific capacitance of 7.5-49.5 F / g at a current density of 0.05-20.0 A / g; And / or, the sodium ion capacitor has an energy density of 16.6-109.4Wh / kg when the power density is 99.75-39900W / kg; And / or, the mass ratio of the active material of the positive electrode to the negative electrode material in the sodium ion capacitor is 1:1-1:2.